Pengembangan Materi Ajar Keterampilan Membaca Berbasis Higher Order Thinking Skills (Hots) - Siti Maisaroh; Erina Maulida Jh; Miftahul Ulum (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2023)
The aims of this study were: 1. Developt teaching materials for reading skills based on Higher Order Thinking Skills (HOTS) 2. Measure the effectiveness of developing teaching materials for reading skills based on Higher Order Thinking Skills (HOTS). This research is a research and development of the ADDIE model which consists of five stages, namely analysis, design, development, implementation, and evaluation. Data collection techniques using observation, interviews, documentation, questionnaires, and tests. After the author designing teaching materials, conduct experiments, analyze all the data, the authors get a summary; 1) Teaching materials for reading skills were developed based on higher order thinking skills (HOTS) in the form of textbooks in accordance with the principle of learning based on higher order thinking skills, student desires, and analysis of student needs. The material is taken from the topic of actual and real problems and phenomena that occur in society. This material consists of ten topics that aim to enable students on obtaining inferential comprehension, evaluation, and appreciation. The product of this resource is the book text contents and methods considered good 76%, it means that the book is suitable for learning. 2) The teaching material is effective for improving speaking skills for students, it is based on the pretest and posttest results increased from an average of 66 % to an average of 81,5 % in posttest. This is supported by the results of questionnaires and interviews that most of the students had good grades and increased. Tujuan penelitian ini adalah: 1. Mengembangkan bahan ajar keterampilan membaca berbasis Higher Order Thinking Skills (HOTS) 2. Mengukur efektivitas pengembangan bahan ajar keterampilan membaca berbasis Higher Order Thinking Skills (HOTS). Penelitian ini merupakan penelitian dan pengembangan model ADDIE yang terdiri dari lima tahap yaitu analisis, desain, pengembangan, implementasi, dan evaluasi. Teknik pengumpulan data menggunakan observasi, wawancara, dokumentasi, angket, dan tes. Setelah penulis merancang bahan ajar, melakukan percobaan, menganalisis seluruh data, penulis mendapatkan ringkasan; 1) Bahan ajar keterampilan membaca dikembangkan berdasarkan keterampilan berpikir tingkat tinggi (HOTS) dalam bentuk buku teks sesuai dengan prinsip pembelajaran berdasarkan keterampilan berpikir tingkat tinggi, keinginan siswa, dan analisis kebutuhan siswa. Materi diambil dari topik permasalahan dan fenomena aktual dan nyata yang terjadi di masyarakat. Materi ini terdiri dari sepuluh topik yang bertujuan agar siswa memperoleh pemahaman inferensial, evaluasi, dan apresiasi. Produk dari sumber ini adalah teks buku, isi dan metodenya dinilai baik 76%, artinya buku tersebut layak untuk dipelajari. 2) Bahan ajar efektif untuk meningkatkan keterampilan berbicara siswa, hal ini berdasarkan hasil pretest dan posttest meningkat dari rata-rata 66% menjadi rata-rata 81,5% pada posttest. Hal ini didukung dengan hasil angket dan wawancara bahwa sebagian besar siswa mempunyai nilai baik dan meningkat.